Physicochemical properties of yogurt synbiotic enriched with bawang Dayak (Eleutherine palmifolia (L) Merr) extract - Andriani, Ria Dewi; Sawitri, Manik Eirry; Widayanti, Vindhya Tri; Manab, Abdul; Rahayu, Premy Puspitawati; Prasasti, Finna; Saleha, Rischa Amalia (Faculty of Animal Science, Universitas Brawijaya, 2024)
Yogurt is a synbiotic yogurt made from a combination of probiotics and prebiotics, so the addition of bawang dayak extract (Eleutherine palmifolia (L) Merr) improved the functional properties of the synbiotic yogurt. The research objective was to analyse the physicochemical properties of yogurt synbiotic enriched with bawang dayak extract. The physicochemical properties, pH, acidity, syneresis and water holding capacity were analysed. This research used a completely randomized design (CRD), which consisted of 4 treatments and 3 replications with various concentrations of bawang dayak extract (T0 = 0%, T1 = 1%, T2 = 4% and T3 = 6%). The main ingredients used were skim milk, fresh milk, yogurt starter (Lactobacillus bulgaricus, Streptococcus thermophilus) and bawang dayak extract. The results of this study showed that the pH, acidity and water holding capacity were not significantly different (p>0.05) among the treatments, while syneresis was highly significantly different (p<0.01) at the T3 (6%) concentration.